Inspirational Principal: Building A Culture of Organization and Spiritual Communication - Suryahim, Iim; Mabruroh, Mabruroh; Supriadi, Supriadi (JURNAL AL-TANZIM, 2023)
Organizational culture is understood as a shared perception adopted by members of an organization, namely a system of shared meaning. A developing organizational culture is critical to support their growth and development in early childhood education. This research aims to understand the role of inspirational school principals in shaping organizational culture and spiritual communication among students. The research was conducted at an early childhood education institution, RA Al-Azhar Pandean Paiton Probolinggo. The research design used was qualitative, with steps involving observation, requesting permission, collecting data from schools, and interviews. The primary data source is field research through interviews with school principals and teachers. Meanwhile, secondary data comes from literature relevant to the identified problems. Data collection methods include interviews, observation, and documentation. The research results show inspirational school principals are essential in shaping organizational culture and spiritual communication. This is achieved through several steps, such as forming teamwork, routine spiritual activities, environmental participation, and program evaluation. Implementing this program implies that an organizational culture that is instilled from an early age can shape the character of students into good individuals with spiritual nuances.